Tinjauan Hukum Islam Terhadap Pemberian Mahar dan Uang Panaik (Uang Belanja) dalam Perkawinan Adat Bugis - Rocky Eric Prianto (Jurnal Ilmiah Kutei, 2025)
In the life of indigenous people, dowry is not the only thing that is a must because in general the family of the prospective groom will also provide panaik money (shopping money), but what will be given panaik money (shopping money) must be meaningful, valuable and valuable. The purpose of this study is to describe and explain the position of dowry and panaik money in Bugis customary marriage law and to describe the views of Islamic law on the implementation of giving dowry and panaik money in Bugis customary marriage law. The data sources used in this study are based on literature, laws and regulations, sources of customary law, and sources of Islamic law. The results of this study are that the customary law marriage process will be valid if it is in accordance with the provisions of local customary law, and the position of panaik money is a pillar, because if there is no panaik money then there is no marriage, and the law of giving panaik money in Islamic law is mubah or allowed as long as there is no element of coercion in the process.